Biochar as a Fertilizer Replacement for Sustainable Agriculture - Niazi, Parwiz; Hekmatullah, Zaland; Mohammad, Mohammad Usman; Monib, Abdul Wahid; Hassand, Mohammad Hassan; Ozturk, Hamidullah; Azizi, Azizaqa; Mansoor, Mujibullah; Akhundzada, Mohammad Shafi; Alimyar, Obaidullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Biochar is a promising solution for pesticide pollution and soil degradation in agriculture. It improves fertilizer efficiency by increasing nutrient availability, and acts as a slow-release fertilizer. Biochar enhances soil fertility by retaining nutrients, and increasing organic matter, water retention, and microbial activity. It also shows potential in pesticide degradation through chemical, and microbial processes. However, the sorption of pesticides on biochar can hinder degradation. Factors like feedstock, pyrolysis temperature, and application rate influence biochar's nutrient retention capabilities. Understanding these factors is crucial for optimizing biochar's effectiveness in agricultural systems.